2016
DOI: 10.1017/s0020818316000047
|View full text |Cite
|
Sign up to set email alerts
|

Judicial Independence and Political Uncertainty: How the Risk of Override Affects the Court of Justice of the EU

Abstract: There is broad agreement in the literature that international courts (ICs) make decisions with bounded discretion in relation to state governments. However, the scope of this discretion, and the determinants of its boundaries, are highly contested. In particular, the central mechanism in separation-of-powers models of judicial politics—the possibility of legislative override—has raised controversy. We argue that the uncertainty that judges face regarding the political reactions to their decisions has important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(156 citation statements)
references
References 53 publications
6
149
0
1
Order By: Relevance
“…Consistently with this, political scientists have shown that the judgments going against mobile citizens correspond to media attention for migration and benefit tourism (Blauberger et al 2018), suggesting that the Court 'reads the morning papers'. This fits a wider trend of political science research suggesting that the Court is responsive to external political pressures and moods (Kelemen 2012;Larsson and Naurin 2016;Martinsen 2015).…”
Section: Introductionsupporting
confidence: 75%
“…Consistently with this, political scientists have shown that the judgments going against mobile citizens correspond to media attention for migration and benefit tourism (Blauberger et al 2018), suggesting that the Court 'reads the morning papers'. This fits a wider trend of political science research suggesting that the Court is responsive to external political pressures and moods (Kelemen 2012;Larsson and Naurin 2016;Martinsen 2015).…”
Section: Introductionsupporting
confidence: 75%
“…In terms of pure legal doctrine, most legal scholars observe a discontinuity in the Court's citizenship jurisprudence or even a reversal, which can hardly be brought in line with earlier, expansive rulings. The two most prominent arguments about political influence on the ECJ focus on EU governments' threats against unwarranted judicial activism -either the threat of non-compliance (Carrubba and Gabel 2015) or of legislative override (Larsson and Naurin 2016). We find plenty of evidence for both threats, but they do not correlate with the evolution of the Court's case law on EU citizenship.…”
Section: Introductionmentioning
confidence: 62%
“…The question of EU citizens' crossborder access to welfare benefits touches upon several core issues of integration, such as EU enlargement, citizens' mobility, the viability of national welfare systems, Eurosceptic parties addressing the topic in a welfare-chauvinist way, as well as citizens' eroding consent with the European integration project. At the same time, the scope of our analysis is clearly more limited than that of general accounts of the Court's jurisprudence (Larsson and Naurin 2016;Carrubba and Gabel 2015;Stone Sweet and Brunell 2012) and also more narrow than studies on the Court's entire citizenship case law (Šadl and Madsen 2016). Theoretically, our aim is not to generally test and refute any of the other explanations of Court behaviour discussed above, but to demonstrate the plausibility and the added-value of an account emphasizing the influence of the broader political context on the Court (for a similar view regarding the complementary character of different mechanisms of political influence, see Larsson and Naurin 2016: 385f.).…”
Section: Research Design Methods and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the politics of the European legal order has of course proliferated since these early debates, bringing new attention to particular legal issue-areas, to quantitative analyses of ECJ judgments and of European law in national courts, and to indepth histories of the reception of European law in particular member states (recently, for instance, Kelemen and Pavone, 2018;Larsson and Naurin, 2016;Martinsen, 2015). Research on the politics of the European legal order has of course proliferated since these early debates, bringing new attention to particular legal issue-areas, to quantitative analyses of ECJ judgments and of European law in national courts, and to indepth histories of the reception of European law in particular member states (recently, for instance, Kelemen and Pavone, 2018;Larsson and Naurin, 2016;Martinsen, 2015).…”
Section: Moravcsik's Liberal Intergovernmentalism and The Europeanmentioning
confidence: 99%